Growth of acid fast L forms from the blood of patients with sarcoidosis. Issue 5 (May 1996) - Almenoff, P. L.; Johnson, A.; Lesser, M.; Mattman, L. H.
Abstract : BACKGROUND: Acid fast cell wall deficient forms (CWDF) of bacteria have been grown from blood, bronchial washings, and ocular anterior chamber fluid from patients with sarcoidosis. A monoclonal antibody raised against Mycobacterium tuberculosis whole cell antigen (H37RV) was used to characterise further CWDF grown from the blood of patients with sarcoidosis. METHODS: Blood from 20 patients with active sarcoidosis and from 20 controls was cultured using methods favourable for the growth of CWDF. Isolates were further characterised by indirect fluorescent antibody analysis using a monoclonal antibody highly reactive with M tuberculosis. RESULTS: CWDF were grown from the blood of 19 of 20 subjects with sarcoidosis. All isolates stained positively with the monoclonal antibody and with a modified Kinyoun stain. No organisms were grown from the blood of controls. CONCLUSIONS: These data demonstrate that CWDF can be grown from the blood of nearly all patients with active sarcoidosis. The results confirm that the organisms are mycobacterial in origin and are similar, if not identical, to M tuberculosis. Their role in the pathogenesis of sarcoidosis is unknown.